Dicrocoelium Egg Identified in an Ancient Cemetery in Kiasar Archeological Site, Northern Iran, Dated Back 247 BC-224 AD - Negar BIZHANI; Abdol Motalleb SHARIFI; Mohmmad Bagher ROKNI; Jean DUPOUY CAMET; Mostafa REZAEIAN; Mohammad FALLAH KIAPI; Niloofar PAKNEZHAD; Faezeh NAJAFI; Gholamreza MOWLAVI (Tehran University of Medical Sciences, 2017)
Background: Along with the newly emergence of paleoparasitology research in Iran, findings of parasites from Northern part of the county have not been reported so far. In this study tracking for the lancet liver fluke dates back 250 BC is addressed. Methods: Samples were taken from grave crypts of the soil layers attached to the pelvic bones from above-mentioned site in 2015. The laboratory examinations were conducted in the Dept. of Medial Parasitology and Mycology, School of Public Health, Tehran University of Medical Sciences, Tehran, Iran. Current rehydration technique using TSP 0.5% was utilized for examining the samples. Results: Out of 10 burial soil samples examined, one individual was seen parasitized with a Dicrocoelium egg. The burial belonged to an adolescent male 20-22 yr old. The egg was in brown color and the length/width parameters of 36×22/5 µm. Parthian coins found in nearby the burials in Kiasar Cemetery, declared the time of the skeleton about 247 BC - 224 AD confidently. Conclusion: Although the possibility of transit infection with D. dendriticum is high, yet the environmental and geographical conditions in that time are in favor of a normal human transmission in northern Iran.